Combined influence of Be and Ca on improving the high-temperature oxidation resistance of the magnesium alloy Mg-9Al-1Zn. (1st July 2017) - Tan, Qiyang; Mo, Ning; Jiang, Bin; Pan, Fusheng; Atrens, Andrej; Zhang, Ming-Xing
Graphical abstract: Highlights: The oxidation resistance of Mg-9Al-1Zn was improved by combined alloying with Be and Ca. Alloying with 20 wt ppm Be plus 0.5 wt.% Ca let to higher oxidization resistance than alloying with 60 wt ppm Be. Combined alloying led to a more oxidation resistant alloy containing less toxic Be. The synergistic effect and mechanism of Be and Ca in improving the oxidation resistance of Mg alloys was discussed. Abstract: The present work showed that the oxidation resistance of Mg-9Al-1Zn at elevated temperatures was improved by combined alloying with Be and Ca. AZ91 alloyed with 20 ppm (wt) Be and 0.5 wt.% Ca had higher oxidization resistance than that of AZ91 containing 60 ppm (wt) Be. The improved oxidation resistance was attributed to (a) the formation of a Be-reinforced compact CaO-MgO composite layer on the alloy surface, and (b) suppressing the grain boundary evaporation of Mg by (i) the elimination of Mg-Al eutectic micro-constituent, and (ii) the increase in thermal stability of the β-Mg17 Al12 due to the Ca alloying.